MULTICULTURAL AND CULTURALLY RESPONSIVE PEDAGOGY IN PRACTICE: A VISUAL ANALYSIS OF INDONESIAN EFL TEXTBOOKS - Nuskhan Abid; Azizah Maulina Erzad; Muhammad Noor Sulaiman Syah (English Review: Journal of English Education, 2025)
This study explores how multicultural values are visually represented in Indonesian English as a Foreign Language (EFL) textbook. The findings reveal that textbook illustrations depict diverse students interacting harmoniously across ethnic, religious, and cultural backgrounds. Key images illustrate inclusive educational environments, interfaith friendships, and culturally respectful behavior. These depictions support students’ language development and shape civic values and intercultural competence. Drawing from theories of multicultural and culturally responsive pedagogy, the study finds that textbooks function as ideological tools that internalize social ethics aligned with Pancasila and Bhinneka Tunggal Ika. This research highlights the importance of visual literacy in language learning and recommends a stronger integration of intercultural values through multimodal and digital representations.